Cefuroxime Prophylaxis in Cardiovascular Surgery: Clinical, Microbiological, and Ecological Impact - Gentry, Layne O. (1992)
To determine the efficacy of cefuroxime as a prophylactic agent against infection, we retrospectively evaluated patients who had undergone cefuroxime therapy for cardiovascular surgery procedures in the years 1987 and 1990. In the 403 evaluable patients (203 in 1987 and 200 in 1990), we noted a postoperative surgical wound infection rate of 3% and a nosocomial infection rate of 3%. These rates have remained constant in 1987 and 1990. Despite more than a 6-fold increase in cefuroxime consumption during this same period, we have not observed a selection for staphylococcal infections in cardiovascular surgery patients, nor have we detected a selection for resistant staphylococci in our institution. Our original criteria that caused us to select cefuroxime for routine prophylaxis—notably its equivalent efficacy and safety as compared with other cephalosporins, and its lack of an adverse impact on the hospital flora—remain valid. (Texas Heart Institute Journal 1992;19:21-5)